The construction of gendered subjectivities of female broadcast professionals within TRT (1964 – 1989) - Akkaya, Özlem. (Thesis (Ph.D.) - Bogazici University. Atatürk Institute for Modern Turkish History, 2013., 2013)
This dissertation studies the construction of gendered subjectivities of the women who worked as broadcast professionals for the Turkey Radio and Television Corporation (TRT), during the period of state monopoly on air between 1964 and 1989. The primary aim of the research is to make visible these women’s agency in the development of radio and TV broadcasting in Turkey, which is usually neglected in conventional accounts about media history. Besides this overall aim, the research particularly attempts to find out the ways female broadcast professionals were incorporated into the state ideology as agents. It pursues this objective by situating these women’s personal narratives within the historical context of the socioeconomic, political and cultural transformation through which Turkey passed from developmentalism to neoliberalism as the dominant state ideology. The research first describes the development of radio broadcasting in Turkey under the state monopoly before the establishment of TRT in 1964 and women’s involvement in this process. Then it questions the influence of the definition of radio and television’s social role as citizen education in the developmentalist period of the 1960s and the 1970s on the women TRT recruited as broadcast professionals, with a focus on these women’s negotiation with the dominant gender ideology sponsored by the state. After that, it examines the implications of the transformation in the state hegemony to neoliberalism as aligned with conservatism in the 1980s both for the discourse on womanhood circulating on the state-governed air and for female broadcast professionals’ participation in the creation of this discourse. The final focus is given to the changes and continuities in the imagery of female broadcast professionals as depicted in the popular culture from the 1970s to the 1980s. The research analyzes women’s engagement with the professional field of broadcasting with an emphasis on their agency in the creation of mediated texts in both time periods. Drawing mainly on female broadcast professionals’ personal narratives, it accepts them not as passive conduits whereby the state ideology was transmitted to audiences, but as active and critical mediators of this ideology. In this way, the study sheds light on the historical interaction between these women’s participation in media production and the circulation of mixed and/or conflicting meanings about womanhood on the state radio and television.
Keywords: Women broadcasters -- Turkey.; Women in television broadcasting -- Turkey.